Minimax Theorems with Bregman Distance in Banach Spaces. (2nd January 2016) - Chuang, Chih-Sheng; Lin, Lai-Jiu
ABSTRACT: Since Bregman distance is a generalized distance function which does not satisfy the triangle inequality nor symmetry, it is important to study minimax theorems in reflexive Banach spaces. Our minimax theorems differ from those in previous literature.